2021
DOI: 10.1186/s40479-021-00146-w
|View full text |Cite
|
Sign up to set email alerts
|

Latent profiles of patients with borderline pathology based on the alternative DSM-5 model for personality disorders

Abstract: Background There have been multiple attempts to try to parse out heterogeneity within borderline pathology by identifying patient subtypes; thus far, these works have yielded few consistent results. Recent developments in the operationalization of borderline pathology may provide new opportunities to identify clinically and conceptually meaningful subgroups of patients. The Alternative DSM-5 Model for Personality Disorders (AMPD) offers a categorical-dimensional operationalization of Borderline… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 60 publications
16
35
0
Order By: Relevance
“…Males were not overrepresented in the externalizing cluster, unlike what was seen in one earlier study with a similar cluster solution [ 2 ]. A similar externalizing cluster has been identified in several other studies [ 2 , 10 , 17 ]. Further, the internalizing cluster was characterized by greater psychic anxiety, stress susceptibility, lack of assertiveness and detachment, and lower adventure seeking than the other two clusters, as well as less undercontrol than the externalizing cluster.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Males were not overrepresented in the externalizing cluster, unlike what was seen in one earlier study with a similar cluster solution [ 2 ]. A similar externalizing cluster has been identified in several other studies [ 2 , 10 , 17 ]. Further, the internalizing cluster was characterized by greater psychic anxiety, stress susceptibility, lack of assertiveness and detachment, and lower adventure seeking than the other two clusters, as well as less undercontrol than the externalizing cluster.…”
Section: Discussionsupporting
confidence: 82%
“…Studies designed with a basis in cluster subgroups of BPD using the hybrid approach have been performed. For example, Gamache et al [ 10 ] found four clusters based on the AMPD, comprising a dimensional component of severity (BPD traits, moderate pathology, and severe pathology), with the moderate pathology cluster separated into two categorical dimensions of impulsivity vs. identity/depressiveness, resembling the externalizing-internalizing findings of previous studies [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations